Constructing Ocean and Polar Governance - Wehrmann, Dorothea; Zimmermann, Hubert (Politics and Governance, 2022)
The governance of ocean and polar regions is among the most relevant challenges in the combat against global environmental degradation and global inequalities. Ocean and polar regions are climate regulators and very much affected by climate change. They are an important source of nutrition for life in and above the sea. At the same time, they are subject to an increasing number of geopolitical and geo-economic conflicts. Due to the lasting virulence of many security issues, economic conflicts, legal disputes, new technological developments, and environmental crises in global marine areas as well as the intricate overlap of sovereign, semi-sovereign, and global commons territories, the relevance of ocean and polar governance is bound to rise. This thematic issue sketches important trends in research on these issues and identifies future avenues of inquiry. In this editorial, we first provide an overview of governance challenges for ocean and polar regions and their relevance for geopolitical and geo-economic conflicts. In a second step, we present the eight contributions that make up the thematic issue by clustering them around three themes: (a) challenges to norm-creation in ocean governance, (b) the impact of territorialisation on governance and the construction of authority, and (c) the effectiveness of regimes of ocean and polar governance.